Konsep Jiwa Setelah Mati Menurut Mullā Ṣadrā - Siti Ikhwanul Mutmainnah (Himpunan Peminat Ilmu-Ilmu Ushuluddin (HIPIUS), 2015)
This article describes Mullā Ṣadrā’s idea to solve a polemic and debate on the resurrection after the death. The debate especially concerns on the resurrection of what: is it the soul or the body which resurrect?For this matter Mullā Ṣadrā offers three concepts 1) the soul is eternal and will be resurrected by a new body, 2) that new body is a result of the soul’s projection from its conduct in the world, 3) the soul will continually walk from one sphere to another without ending to God.